The use of adaptive neuro-stimulation for rebalancing posture and muscular tone in a soccer team - Barassi, G.; Bellomo, R. G.; Porreca, A.; Giannuzzo, G.; Giannandrea, N.; Pezzi, L.; Crudeli, M.; Visciano, C.; Saggini, R. (The Journal of Sports Medicine and Physical Fitness, 2019)
BACKGROUND: Posture and somatic structure could positively influence athletic gestures for their biomechanical implications. Working on neuromuscular activity, offers the possibility of intervention on postural control. The aim of this study was to demonstrate the possibility of interacting with the human body system through the spinal reflex pathway, starting from the stimulation of cutaneous receptors. METHODS: Twenty soccer players were recruited: all were male aged 25.5±10.6 years. Patients were divided using a single-blind criterion into two groups, each containing ten subjects. The experimental group was treated with 2 pre-set programs 4 times a week with an adaptive neuro-stimulation (ANS) able to interact with cutaneous receptors through an ENF Physio® device with a range of electrical frequency of about 15-350 Hz; the placebo-controlled group received the treatment with the device switched off. Patients performed a myometric evaluation with the MyotonPRO® system and a postural one with the Rarog software at T0 before the treatment and at T1 after the four-week treatment. RESULTS: After our intervention, we identified an improvement in muscular tone, in particular in the hamstring muscles (17.69%, right P<0.01 / left P<0.05) and a rebalancing of the principal bone points in the postural system (shoulder 71%, P<0.05, hips 65.6%, P=0.056, sagittal AP and frontal LL center of gravity, respectively 40%, P<0.05 and 52.7%, P=0.01). CONCLUSIONS: In conclusion, we could hypothesize the usefulness of an ANS to act on these parameters. ANS could be used not only for treatment of injuries but also in the field of prevention.